A trajetória da educação infantil na UFSM: 23 anos de história do Ipê Amarelo - Silva, Vania Maria Almeida da (2012)
This study sought to understand the history of the establishment and development of the Center for Early Childhood Education Ipê Amarelo at the Federal University of Santa Maria, seeking evidence of its recent history, for, as appropriate, to analyze the identity of this space in the University. In the theoretical framework was aimed the contextualize the childhood History the Child and Early Childhood Education as well as the contributions of Public Policy and Legislation for the advancement of early childhood education in the country. It was also to demonstrate the route of the College Creches in Federal Universities, discussion of its role and academic identity, and in particular the creation of the Center for Early Childhood Education Ipê Amarelo and the prospects of maintaining this space at the University. The methodology adopted was based on the approach of historical-cultural, based on the concepts of interaction Vygotskyanas subject-world. Research in this approach allowed us to understand the phenomenon as part of a larger historical process, relating it with the social and cultural transformations produced by mankind. Was used as data collection techniques to document analysis, through institutional documents and legislation, semi-structured interviews with individuals involved in the implementation and establishment of the institute audio recording. The research results led to conclude that throughout the process of formation and development of the Ipê Amarelo in the University, many were trodden paths, different conceptions permeated the managements of the Center, who followed the historical evolution of Early Childhood Education in Brazil, and Public Policy Legislation. It was noticed over the years significant changes in conceptions of Children, Child and Early Childhood Education, and the pursuit of his teachers at the University by a space that allied education and care of children with training, because it is historically an area of educational practices. Through the constant struggle of the current management team for the recognition and consolidation of their identity, won the acknowledgment of the Ipê Amarelo as a Unit of Early Childhood Education, character education, where the child is seen as subjects of rights, the protagonist of his time and its history. The Unit is currently seeking to make the link between education, research and extension in line with the objectives of the University, thus consolidating its academic role and identity.